Modulating defect density of NiO hole transport layer via tuning interfacial oxygen stoichiometry in perovskite solar cells. (February 2022) - Haider, Muhammad Irfan; Fakharuddin, Azhar; Ahmed, Safeer; Sultan, Muhammad; Schmidt-Mende, Lukas
Graphical abstract: Highlights: A systematic control of oxygen stoichiometry at NiOx/perovskite interface by thermal treatment. PSCs with r-NiOx show 20% improved PCE and extended stability in comparison to other counterparts. A higher defect density at the o-NiOx/perovskite interface leads to poor performance and faster degradation. Abstract: The role of oxygen stoichiometry towards the surface properties of NiOx and its influence over perovskite film morphology, band alignment and charge extraction at NiOx /MAPbI3 interface in inverted perovskite solar cells (PSCs) is analyzed. The oxygen stoichiometry was systematically tuned via thermal treatment of NiOx film in oxygen-rich (o- NiOx) and oxygen-deficient (r- NiOx) atmospheres. These processing conditions impact the defect density and conductivity of NiOx films and thus on the rates of surface recombination, the power conversion efficiency (PCE) and the device stability. We note that the PSCs with r- NiOx show a 20% improvement in PCE in comparison to o- NiOx counterparts. Room-temperature stability measurements for a period of several months demonstrates that the r- NiOx/MAPbI3 interface prolongs the device stability and retains 95% of its initial PCE, whereas a higher defect density due to the presence of excess oxygen at the o- NiOx/perovskite interface leads to faster degradation.